«Ситуация постмодерна» в исторической наук:проблема восприятия научным сообществом - Кравченко, И. С. (ун-т ім. В. Н. Каразіна, 2010)
В статье подчеркивается, что «ситуация постмодерна» в исторической науке постсоветским научным сообществом была воспринята как «вызов». Такая трактовка спровоцировала рост интереса к проблемам классической философии истории. Однако, «постмодернистский историографический проект», ассоциирующийся с кризисом в исторической науке и отвергающийся как несостоятельный, стал частью современного отечественного интеллектуального пространства. In this paper it is highlighted that “postmodern condition” was recognized as “the challenge” by post-soviet academic community. This perception provoked the growth of interest in problems of classic philosophy of history. Postmodern historiographical project, however labeled as related to the crisis of historical science and rejected as failed, has become the part of contemporary post-soviet intellectual space. Key words: postmodern condition, post-soviet academic community, crisis of the historical science.
Keywords: ситуация постмодерна; отечественное академическое сообщество; кризис в исторической науке; postmodern condition; post-soviet academic community; crisis of the historical science